Efeitos do ensino de movimentos orofaciais sobre a acurácia do ecoico em crianças com TEA - Corrêa, Karina Faraco (Universidade Federal de São Carlos, 2024)
Applied Behavior Analysis (ABA) is a science dedicated to the assessment and modification of behaviors based on the principles of operant conditioning. Behaviors are understood as the results of the interaction between the individual and the physical and social environment in which they are embedded. The echoic is a type of verbal operant that involves emitting a vocal response identical to a previous auditory stimulus, establishing an identity relation between the antecedent and the response. The effectiveness of the echoic depends on the accuracy of the response, with accuracy defined as the extent to which the results approximate the true value or established standard. In Autism Spectrum Disorder (ASD), the lack of functional verbal behavior is common, and these deficits can be addressed through behavioral interventions such as Discrete Trial Training (DTT). This approach involves structuring the environment with simple instructions and focusing on the essential characteristics needed for successful task execution. Imitation, a fundamental operant for language and communication learning, is considered a prerequisite for the development of the echoic, but it is not sufficient by itself to guarantee the learning of the echoic. Therefore, it is crucial to ensure that children with ASD demonstrate imitation skills and that their oral movements are appropriate and well-executed to facilitate speech learning. It is important that the development and coordination of the orofacial structures are intact, including articulatory, laryngeal, and respiratory movements, for effective speech production. In this regard, the adequacy of the stomatognathic structures involved in speech significantly contributes to the improvement of this skill. To provide the community with a tested teaching method, the aim of this study is to examine the effect of teaching orofacial movements on the accuracy of the echoic in children with ASD. The study involved four children diagnosed with Autism Spectrum Disorder, levels 1 and 2, aged 2, 3, and 5 years, from both genders. The baseline of the Generalized Echoic Test was applied, which was used as a comparison base for tracking progress during subsequent teaching sessions. The errors identified in the mentioned protocol were taught one by one, demonstrating the model for executing the oral movement from the articulatory point, using only visual cues without the auditory component. In the initial test applications, the participants did not show good results regarding speech accuracy. However, after teaching orofacial movements related to the articulatory points of the identified errors, there was an improvement in the behavior, aiding in the precise execution of speech. Given the data found and presented in this work, it can be concluded that teaching orofacial movements helped the research participants achieve 100% speech accuracy in the requested echoic tasks.
Effects of teaching orofacial movements on echoic accuracy in children with ASD
Keywords: Autismo; Movimentos orais; Acurácia; Ecoico; Análise do comportamento aplicada; Imitação motora; Autism; Oral movements; Accuracy; Echoic; Applied behavior analysis; Motor imitation; CIENCIAS DA SAUDE::FONOAUDIOLOGIA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM